Smart trust : Creating prosperity, energy and joy in a low-trust world - Stephen M R Covey (Simon & Schuster, 2012)
Trust continues to be the most pivotal element needed in successful relationships-from personal to political to business. Smart Trust shows how to develop optimal trust relationships, revealing how this approach been successfully used already for both organizations and on a personal level, and offering targeted advice on how to make trust relationships work in your business and your life.